Effect of microwave irradiation on the blow fly Chrysomya megacephala (F.) (Diptera: Calliphoridae) - Sripakdee D. (2014)
Chrysomya megacephala (F.) is a blow fly species of medical importance, being pestiferous and a mechanical carrier of various microorganisms to human food. Various strategies to reduce the fly population in endemic areas are needed. We investigated the effects of microwaves at 2,450 MHz, with third-instar exposure times of 7, 10, 15, 30 and 60 seconds on the larvae. Survival of the larvae was monitored by their emergence. About 60% of the larvae lived after 7 seconds of exposure, most died by 15 seconds, and all were dead at 30 and 60 seconds. The number of survivals decreased with increasing exposure times. This indicates the effect of microwave irradiation on fly larval survival.